Drug-Induced Erythema Multiforme - Peeyush Shivhare; Naqoosh Haidry; Anka Sharma; Deepali Agrawal; Abhishek Gupta; Shalini Subramanyam (Hindawi Limited, 2023)
Erythema multiforme (EM) is an acute inflammatory, mucocutaneous, psychosomatic, and vesiculobullous condition that varies from minor to major forms. The acral distribution of target lesions is a characteristic of this condition. The aetiology of erythema multiforme is multifactorial. 90% of the cases are triggered by a herpes infection, whereas 10% occur secondary to drug intake. The offending drugs include nonsteroidal anti-inflammatory drugs, antibiotics, and anticonvulsants. The present case series discusses four cases of drug-induced erythema multiforme and their management.